USM-RIKKYO UNIVERSITY JAPAN SHARE EXPERTISE ON TOURISM - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 March 2016 – The Sustainable Tourism Research Cluster (STRC) Universiti Sains Malaysia (USM) together with Rikkyo University in Tokyo, Japan recently organised an ‘International Symposium On Migration And Tourism Infrastructure In Global Cities’ here with the aim of sharing the research findings of the two universities.